Application of microwave-assisted orange peel digestion in lithium-ion battery recycling - Nawfal Alimullah Marican (Nanyang Technological University, 2022)
As the demand for lithium-ion batteries continues to increase year on year, various concerns begin to arise, such as the possible shortage of important metals such as lithium, cobalt, manganese and lithium. The disposal of these batteries which are not commonly recycled, is also beginning to have significant impacts on the environment. As such, it has become increasingly important to promote the recycling of these batteries to counter the issues listed above. Hydrometallurgy is a conventional method using in recycling, it includes 2 important factors: acid and reducing agents. Biomass, especially orange peels, contains a significant amount of organic acid (citric acid) and antioxidant (ascorbic acid, pectin, limonene) which can be utilized in hydrometallurgy. This research project aims to digest essential oil from orange peel by using a microwave-assisted pre-treatment method, which is shorter in overall processing time than hydrolytic method. The effectiveness of the microwave digestion was tested using characterization techniques such as Ferric Reducing/Antioxidant Power (FRAP) assay kit and 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) to identify the reducing/antioxidizing capabilities of the pre-treat solution. The microwave-assisted pre-treatment and hydrolytic leaching process were optimised mainly by varying the time and temperature parameters. Our results showed that the microwave-assisted pre-treatment process could reduce the processing time for pre-treatment from 72 hours to just 35 minutes. After optimization of the pre-treatment process, the battery leaching process was also optimised to reduce processing time from 24 hours to 8 hours while also reducing the operating temperature from 90°C to 60°C. We also managed to successfully recover important metal ions through precipitation. The overall leaching efficiency was also maintained at around 90% for the 4 important metals mentioned above. This reduction in processing time aims to make the recycling of lithium-ion batteries, through recovery of important metals, into a more enticing and less costly endeavour so that it may be more commonly adopted.